Health And Marketing Protocols For Msme Angkringan Traders In Diro Village Bantul - Idiani Darmawati; Ratna Indriawati; Iswanto Suwarno (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
Micro, Small and Medium Enterprises is one of the fields that makes a significant contribution to spurring Indonesia's economic growth. SMEs in Indonesia still face various promotional and marketing problems. Angkringan is a place that sells simple food that does not recognize social strata. As information and communication technology develops, it has been used for online product marketing. Online product marketing has many advantages, namely wide coverage, does not know time and space, can be done anytime and anywhere. Pak Nardi's Angkringan doesn't understand online marketing strategies and health protocols, so it needs to get training. With education on health protocols and online marketing, it is hoped that partners can implement health protocols well and can manage online marketing accounts independently. This activity aims to find strategies to improve the implementation of health protocols and increase online sales turnover. The methods used are offline and online mentoring and education. As a result of this assistance, angkringan business actors can improve their health protocol discipline and can market their products online, so that sales turnover increases. The conclusion obtained is that by providing educational assistance on health protocols and online marketing strategies, business actors can improve health protocol discipline and can market their products online, so that sales turnover increases.